Dynamic relationships between technological innovation and Income Distribution (2011)
This study analyzes how human capital accumulation and technological change influence both Economic growth and income inequality. By means of theorical antecedents, empirical antecedents, stylized facts and a three sectors model, we explain the dynamic of relationship between endogenous Economic growth and income distribution when human capital and technological change are complementary. The results identify that Economic growth process affects income distribution through human capital returns and the composition that human capital represents in the total actives of the consumers. Key words: economic growth, income distribution, technological change, human capital.